Rhetorical style the uses of language in persuasion - Fahnestock, Jeanne, 1945- (New York : Oxford University Press, 2011)
A comprehensive guide to the language of argument, Rhetorical Style offers a renewed appreciation of the persuasive power of the English language.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Persuasion (Rhetoric); English language -- Rhetoric; English language -- Style